Comparative Study of Polymer Composites with Cellulose Microfibers from Different Plant Resources - Jyoti Giri; Rameshwar Adhikari; Janak Sapkota (Advances in Polymer Technology)
Wheat stalk (W), Fosro (F), Nigalo with waxy layer (NW), and Nigalo without waxy layer (NWo) were used to extract microcrystalline cellulose (MCC), the xMCC (where x represents origin such as W, F, NW, and NWo) by thermochemical and mechanical treatments. About 10 wt% of xMCC and commercial MCC (C-MCC) were solution casted with ethylene oxide-epichlorohydrin (EO-EPI) to prepare microcomposites. The xMCC and cryo-fractured composites were observed by scanning electron microscopy, and the mechanical properties of the composites were measured by dynamic mechanical analysis to observe the effect of fillers on viscoelastic properties. The results concluded that the xMCCs are homogeneously dispersed in the EO-EPI polymer matrix, which reinforced the viscoelastic and mechanical properties in EO-EPI composites, and reinforcement is dramatically high with NWoMCC compared to NWMCC, WMCC, FMCC, and C-MCC.